The girl and the spider [videorecording (DVD)] - Zürcher, Ramon, 1982-; Zürcher, Silvan; Confurius, Henriette, 1991-; Amuat, Liliane; Lardi, Ursina, 1970-; Giger, Flurin (Cinema Guild, 2022)
As her roommate Lisa prepares to move out of their apartment, Mara contemplates the end of an era. Furniture is moved, walls painted, cupboards built. Amid all the hustle and bustle, secret longings and desires come to the surface and coalesce around the roommates as well as around Lisa's mother Astrid, the movers, the girls' old neighbors, the neighbors' cat, Lisa's new neighbor and an ever-expanding cast of characters. Day turns into night and one final party in the apartment. When the last box is moved, the fragments of their lives remain. This is the second installment in a trilogy about human togetherness, a ballad about the need for closeness and the pain of separation.